Knowledge and self-management practices among type II diabetes patients: a study in Gatundu town in Kiambu, Kenya - Kyalo, Caroline K.; Nyamongo, Daniel S.; Ngugi, Benjamin M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Type-2 diabetes mellitus is recognized as a key non-communicable disease affecting over 425 million world-wide, with only half of them currently diagnosed. The most crucial risk factor for mortality associated with type-2 diabetes is poor adherence to the prescribed medication. Methods: A cohort study design was used to study 98 type 2 diabetes patients in Kiambu County. Consecutive sampling method was used. The collection of data utilized a pre-designed and piloted structured questionnaire. Quantitative data analysis was conducted using SPSS version 26.0 and correlation between the total count of the remaining diabetic medication and the blood sugar after one month follow-up was assessed. Univariate logistic regression was conducted in assessing the association between each of the predictor variables and the two main outcome variables (adherence to medication and glycemic control). A multiple logistic regression model was constructed for each of the two outcome variables. Results: 31 (31.6%) of the study subjects were between 60-69 years, 70 (71.4%) were married and 66 (67.3%) were female. In addition, 37 (37.8%) had diabetes for more than 8 years, 70.6% had hypertension and 83.7% were prescribed oral hypoglycaemic agents as initial treatment. Majority of the respondents constituting 80.7% had high adherence to prescribed diabetes medication regimen, knowledge on diabetes treatment (p=0.009) and detecting low blood sugar levels through signs and symptoms and manage (p=0.001) had significantly association with adherence to antidiabetic. Conclusions: Diabetic patients who have knowledge on diabetes and its management, those who stop alcohol and cigarette smoking and those who understand hypertension are more likely to adhere to diabetic treatment.